Interakcije med zdravili za zdravljenje depresivne motnje in drugimi zdravili - Roškar, Robert (Farmacevtski vestnik, 2006)
Adverse interaction between antidepressants and other drugs are described in this article. Tricyclic antidepressants and selective serotonine reuptake inhibitors (SSRI) are frequently involved in serious drug interactions. Pharmacokinetic interactions based on drug metabolism occur most often for SSRI. Especially fluvoxamine and fluoxetine are highly potent inhibitors of multiple cytochrome P450 enzymes, which are also important metabolic pathways for many other drugs. Serious adverse effects (serotonin syndrome) based on pharmacodynamic interacions may also occur if a serotonin agonist is coadministrated with SSRI. For tricyclic antidepressants are characteristic pharmacodynamic interactions, but also pharmacokinetic interactions with otherdrugs are clinically important. The herb St Johnćs wort (Hypericum perforatum), which has also an antidepressive effect, interacts with many other drugs
Keywords: antidepresivi; drug; interakcije; zdravila